2020
DOI: 10.1094/phyto-11-19-0433-r
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Asian Rice (Oryza sativa) Genotypes Reveals a New Source of Resistance to the Root-Knot Nematode Meloidogyne javanica and the Root-Lesion Nematode Pratylenchus zeae

Abstract: The sedentary root-knot nematodes, Meloidogyne spp., and the migratory root-lesion nematodes, Pratylenchus spp., cause significant yield losses, particularly in aerobic and upland rice production systems. Recently, the Asian rice Oryza sativa accessions LD 24 and Khao Pahk Maw (KPM) were shown to be highly resistant to M. graminicola. In this study, we have analyzed the responses and broadness of resistance of these two rice genotypes to another root-knot nematode M. javanica and a root-lesion nematod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The number of nematodes in Tetep were significantly lower at all the time points as well as in 100 grains compared with Nipponbare, which indicates that the resistance in Tetep may be associated with the reduced numbers of invasion, development, and reproduction of A. besseyi . The same resistance mechanisms were also observed in previous studies on cultivars resistant to other nematodes ( Linsell et al, 2014 ; Khanam et al, 2018 ; Lahari et al, 2020 ; Nzogela et al, 2020 ).…”
Section: Discussionsupporting
confidence: 85%
“…The number of nematodes in Tetep were significantly lower at all the time points as well as in 100 grains compared with Nipponbare, which indicates that the resistance in Tetep may be associated with the reduced numbers of invasion, development, and reproduction of A. besseyi . The same resistance mechanisms were also observed in previous studies on cultivars resistant to other nematodes ( Linsell et al, 2014 ; Khanam et al, 2018 ; Lahari et al, 2020 ; Nzogela et al, 2020 ).…”
Section: Discussionsupporting
confidence: 85%
“…However, the effects of KSL8 can be overridden in the presence of the immune receptor MG1, which is segregating among tropical japonica, indica, and aus cultivars, but not temperate japonica cultivars (Dimkpa et al, 2016; Wang et al, 2023). This intracellular NLR immune receptor was previously shown to confer strong resistance to the RKNs M. graminicola and M. javanica upon recognition of nematode attack through a hypersensitive response (Lahari et al, 2020; Wang et al, 2023). We found that rice cultivars carrying MG1 are strongly resistant to M. incognita as well, with nearly zero galling in cultivars LD24 and Khao Pahk Maw (two-tailed t-test relative to cv.…”
Section: Resultsmentioning
confidence: 99%